The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1590/s2237-96222023000100019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intimate partner violence in Mato Grosso do Sul state, Brazil, 2009-2018

Abstract: Objective: to analyze intimate partner violence (IPV) in Mato Grosso do Sul state, Brazil, with emphasis on physical violence. Methods: this was a cross-sectional study applying multiple correspondence analysis (MCA) to records retrieved from the Notifiable Health Conditions Information System covering the period from 2009 to 2018. Results: of the 9,950 notifications registered, 91.8% were notifications of physical violence; higher rates were found in young females (189.2/100,000), who had up to incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A Brazilian study based on notifications from a state on violence against women observed a predominance of IPV; young victims with a partner, low education and indigenous women had five times greater risk of suffering IPV. The occurrence of violence was more expressive in the border region (Santos & Carmo, 2023), that is, far from large centres or in remote regions, as pointed out in the review.…”
Section: Discussionmentioning
confidence: 60%
“…A Brazilian study based on notifications from a state on violence against women observed a predominance of IPV; young victims with a partner, low education and indigenous women had five times greater risk of suffering IPV. The occurrence of violence was more expressive in the border region (Santos & Carmo, 2023), that is, far from large centres or in remote regions, as pointed out in the review.…”
Section: Discussionmentioning
confidence: 60%
“…O principal local de ocorrência das agressões foi a residência, coincidindo com resultados encontrados por Santos e Carmo. 14 Dessa forma, evidencia-se que a violência doméstica ainda é muito prevalente no Brasil e sua ocorrência representa não só um fenômeno social mas também um problema de saúde pública. 19 Um estudo realizado na Turquia com uma amostra composta exclusivamente de idosos constatou que a maior parte dos casos teve recorrência da violência, 22 assim como a pesquisa de Santos et al, 14 com amostra restrita a mulheres.…”
Section: Discussionunclassified
“…14 Dessa forma, evidencia-se que a violência doméstica ainda é muito prevalente no Brasil e sua ocorrência representa não só um fenômeno social mas também um problema de saúde pública. 19 Um estudo realizado na Turquia com uma amostra composta exclusivamente de idosos constatou que a maior parte dos casos teve recorrência da violência, 22 assim como a pesquisa de Santos et al, 14 com amostra restrita a mulheres. O presente estudo, no entanto, demonstrou resultado divergente das pesquisas citadas.…”
Section: Discussionunclassified
See 2 more Smart Citations